Internship Program Effectiveness: A Work Readiness - Dewi Sukmawati (Universitas Muhammadiyah Malang, 2022)
In entering the world of work, it is necessary to increase self-capacity and the ability to be able to compete in the digital economy era. Internships are a form of student learning to practice their skills and knowledge in a professional environment. This research aims to explain internship program effectiveness with university graduate’s work readiness. This research kind of explanatory research using accidental sampling techniques method as the sampling technique. This research analyzed by using SmartPLS 3.0 program. The result of this research indicate that internship experience has a positive and significant influence toward student work readiness.